Worn out or worn in? How cosmetic wear affects semantic appraisals of materials - Debra Lilley; Alan Manley; Ben Bridgens; Karl Hurn; Vicky Lofthouse (2016)
The aesthetics of material performance within design is typically only considered up to the point of sale, a false end state in which the ‘newness’ of the product is protected by the hermetic packaging in which it is sold. Beyond this, the ‘ageing’ of a material is thought of only in terms of utility or easily measured technical parameters such as durability or toughness, and rarely reflects upon, or accounts for, the users experiential relationship with the material. Here, we explore changes in tactile and visual perceptions when sample materials have been artificially aged through the application of a taxonomy of damage observed from real world products. This paper argues that to expand our current knowledge in material culture and to assist in providing a more nuanced understanding of the user’s long-term relationship with materials, we, as designers, need to observe, record and reflect upon attitudinal reactions to aged and used materials.